2016
DOI: 10.1099/mic.0.000213
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Porphyromonas gingivalis iron-binding protein PG1777 in oxidative stress resistance

Abstract: Whole genome sequencing of the response of Porphyromonas gingivalis W83 to hydrogen peroxide revealed an upregulation of several uncharacterized, novel genes. Under conditions of prolonged oxidative stress in P. gingivalis, increased expression of a unique transcriptional unit carrying the grpE, dnaJ and three other hypothetical genes (PG1777, PG1778 and PG1779) was observed. The transcriptional start site of this operon appears to be located 91 bp upstream of the translational start, with a potential 210 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Surprisingly, these anaerobic pathogens, including P. gingivalis , have also been reported in supragingival plaque, saliva and mucosa samples 9 , 10 , which are thought to be more micro-aerobic environments in the oral cavity. Several proteins have been reported to participate in the resistance to oxidative stress in P. gingivalis 11 14 and they may promote the survival of P. gingivalis under micro-aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, these anaerobic pathogens, including P. gingivalis , have also been reported in supragingival plaque, saliva and mucosa samples 9 , 10 , which are thought to be more micro-aerobic environments in the oral cavity. Several proteins have been reported to participate in the resistance to oxidative stress in P. gingivalis 11 14 and they may promote the survival of P. gingivalis under micro-aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyromonas gingivalis wild‐type strain, W83 , was used for this study and grown as previously described (McKenzie et al., 2016). Briefly, P. gingivalis was first streaked onto BHI agar supplemented with 5% (v/v) sheep blood and incubated at 37°C for 5–7 days under anaerobic conditions (10% H 2 , 10% CO 2 , 80% N 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Porphyromonas gingivalis wild-type strain, W83, was used for this study and grown as previously described (McKenzie et al, 2016).…”
Section: Bacterial Growth Conditionsmentioning
confidence: 99%
“…A recent study reported that P. gingivalis iron-binding protein PG1777 was associated with resistance to oxidative stress (McKenzie et al, 2016). Under prolonged oxidative stress, the expression of a unique gene cluster grpE-dnaJ-PG1777-PG1778-PG1779 increased in P. gingivalis, and the recombinant PG1777 protein exhibited iron-binding properties and protected DNA from degradation.…”
Section: Resistance To Ros-mediated Killingmentioning
confidence: 99%